2016
DOI: 10.1590/1806-9061-2015-0111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Influenza A, West Nile and Newcastle Disease Viruses in Birds from the Pantanal Wetlands of Mato Grosso, Brazil

Abstract: The Pantanal is the world's largest wetland biome with a seasonal flood pulse that attracts a great diversity of birds, many of which are migratory. Birds can be natural reservoirs Influenza A, West Nile and Newcastle Disease viruses. However, the occurrence of carriers for these viruses in the Pantanal was not verified yet. The present study evaluated the occurrence of natural infection by Influenza A, WN and ND virus of birds in the municipality of Poconé, a subregion of the Pantanal in the state of Mato Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…13,14 In comparison, studies in South America have found an overall prevalence of 0.21% in Anseriformes (range: 0.25-0.86%) and 0.32% in Charadriiformes (range: 0.21-3.80%) (Table 3). 33,[35][36][37][38][39][40][41][42][43][44] It is worth noting that Mathieu et al stands out among South American studies for having found a slightly higher AIV prevalence (3.8%), which is probably related to the fact that this study investigated gulls that had been found dead, as opposed to actively capturing healthy birds in their natural habitat. 36 The reasons as to why South American wild birds appear to have a lower prevalence of AIV are unclear, and future studies will be necessary to confirm whether this is a widespread pattern and identify possible causes, or to dismiss the possibility that this reflects differences in sample collection season or storage.…”
Section: Recent Studies Of Aiv In South Americamentioning
confidence: 76%
“…13,14 In comparison, studies in South America have found an overall prevalence of 0.21% in Anseriformes (range: 0.25-0.86%) and 0.32% in Charadriiformes (range: 0.21-3.80%) (Table 3). 33,[35][36][37][38][39][40][41][42][43][44] It is worth noting that Mathieu et al stands out among South American studies for having found a slightly higher AIV prevalence (3.8%), which is probably related to the fact that this study investigated gulls that had been found dead, as opposed to actively capturing healthy birds in their natural habitat. 36 The reasons as to why South American wild birds appear to have a lower prevalence of AIV are unclear, and future studies will be necessary to confirm whether this is a widespread pattern and identify possible causes, or to dismiss the possibility that this reflects differences in sample collection season or storage.…”
Section: Recent Studies Of Aiv In South Americamentioning
confidence: 76%
“…Viral shedding of low pathogenicity AIVs from chickens showed a peak at one to two days post-inoculation followed by rapid decline to low viral titres between three and seven days post-inoculation (16). A previous survey carried out on wild birds in the Pantanal region of Mato Grosso reported no detection of AI or ND (22).…”
Section: Discussionmentioning
confidence: 87%
“…Over the past 15 years, we have conducted influenza surveillance in wild birds at various sites in Brazil, including shorebirds at Lagoa do Peixe National Park (PNLP) and the Amazon region. Previous studies have described the genetic diversity and distribution of A(H2N2), A (H6N1), A(H9N2) and A(H12N5) AIVs in the south of Brazil [9], a lack of detection of viruses in southern grasslands, the northeastern and Pantanal wetlands [10][11][12], and identified A (H11N9) viruses in migratory shorebirds wintering in the Amazon [13]. Much remains to be learned about influenza in this region of the world, particularly with the spread of A(H5N1) viruses.…”
Section: Introductionmentioning
confidence: 99%